Unravelling Second-Order Concepts in South African History Textbooks (Yesterday & Today Journal for History Education in South Africa and abroad, 2024)
This paper explores the progression of second-order concepts in seven purposively sampled South African CAPS-compliant history textbooks. History knowledge encompasses both the substantive and procedural knowledge types, with second-order concepts forming an integral component of the latter. Textbook writers and educators use this knowledge in their domains without a predetermined trajectory. These concepts are not mere skills but fundamental notions guiding historical practice. Their meaningful integration into learning materials forms a necessary toolkit for historical inquiry. Drawing from a broader PhD study, a Bernsteinian (1990) framework and the ‘big six’ concepts articulated by Seixas and Peck (2004) are used to analyse the content of seven chapters, one per book, telling the story of the history of South Africa across grades three to nine in the foundation, intermediate, and senior phases of the South African school curriculum. A continuum was populated, articulating the strengths of the second-order concepts ranging from a powerful presence to those weakly incorporated. The findings indicate a sporadic presence of the six concepts—historical significance, continuity and change, cause and consequence, historical perspectives, and the moral dimension across the textbooks. There is a more inclusive focus in the senior grades and less so in lower grades. The concepts also lack continuous and cumulative development. If these ‘structural’ historical concepts provide the basis for historical thinking, it is unclear how they advance through the grades with increasing levels of complexity. The methodology of history is thus not a universal or one-size-fits-all endeavour but an iterative process inculcating concepts that are nuanced and inherently abstract.
Keywords: Content analysis; Textbooks; Procedural knowledge; Substantive knowledge; Second-order concepts; Progression